A Bibliometric Examination of Studies on Corporate Tax Avoidance Utilizing Vosviewer Software - Dian Sulistyorini Wulandari; Nur Cahyonowati (Jurnal Proaksi, 2024)
The field of corporate tax avoidance is dynamic, with new theories, methods, and empirical findings emerging over time. As tax laws evolve and corporate practices adapt, researchers continually seek to refine understanding of the drivers and consequences of tax avoidance. This research endeavors to systematically analyze and demonstrate bibliometric data using VOSViewer, providing a comprehensive guide for first-time users. By employing mapping tools within VOSViewer, the study examines the trends and evolution of corporate tax avoidance over five years (2018–2023). Utilizing qualitative descriptive methodology, the research presents a detailed network visualization of the subject matter. A search of relevant published journals yielded 1000 articles spanning from 2018 to 2023, categorized into five groups based on publication year. Analysis revealed a total of 180 articles focused on corporate tax avoidance during this timeframe. The study concludes that corporate tax avoidance is an interdisciplinary field ripe for exploration, offering numerous opportunities for innovative research. It is anticipated that this study will serve as a valuable resource for researchers seeking to delve into this topic and determine future research directions.